Opening the gifts and treasures of relationship in residential child care - Carey Morning (Scottish Journal of Residential Child Care)
This paper is about the initial phase of a development project at a residential school in Scotland. It asks us to consider the inner lives of children and those who work with them, and to find ways to create a community which will engender a holistic evolution in all its members. Our work is a journey to help wounded children encounter, believe in, and develop what is the very best in them. We are asked to bring children the very best we have, our treasure, so that they can look at our gifts as in a mirror, and see that they are a precious gift to the world.